1996
DOI: 10.1164/ajrccm/154.3_pt_2.s119
|View full text |Cite
|
Sign up to set email alerts
|

National Asthma Education and Prevention Program Working Group Report on the Financing of Asthma Care

Abstract: The financing of asthma care is the third topic of the National Asthma Education and Prevention Program Task Force Report on the Cost Effectiveness, Quality of Care, and Financing of Asthma Care. This working group explored the effects of financing on access to services, treatment of asthma, and potential health outcomes. Over the course of a year, the working group collected and analyzed information pertaining to the various types of public and private health care financing mechanisms, including both insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A similar recommendation was made in 1996. 12 Public and private funding agencies should use their influence to move the asthma research community toward standardization of definitions, although arriving at such definitions is no easy feat, because it requires consensus and acceptance from multiple stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…A similar recommendation was made in 1996. 12 Public and private funding agencies should use their influence to move the asthma research community toward standardization of definitions, although arriving at such definitions is no easy feat, because it requires consensus and acceptance from multiple stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the "National Asthma Education and Prevention Program Task Force Report on the Cost Effectiveness, Quality of Care, and Financing of Asthma Care" failed to mention air pollution as a factor in patient admissions for asthma. [20][21][22] It seems that current data from epidemiological and toxicological studies have not yet been translated into a general understanding and emphasis by physicians caring for patients with asthma. Since there is no skin test for air pollution exposure, it all too often goes unrecognized as an important factor in asthma exacerbations.…”
mentioning
confidence: 99%
“…While attempts to improve quality and reduce the financial costs of asthma are now commonplace in managed care, 19 there is little published evidence that these programs have been effective 20 . Previous research on the relationship between the financing of asthma care and quality of care found little empirical evidence and therefore a significant need for further understanding of this topic 21 …”
mentioning
confidence: 99%